2nd Independent Science Panel Meeting, Copenhagen, Denmark, 3–4 May 2012 - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
In May 2012 the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) held its second Independent Science Panel meeting in Denmark.